The Effects of Diabetes Mellitus Comorbidities on the Risk of Treatment Failure in Tuberculosis Patients: A Meta-Analysis - Sri Iswahyuni; Ani Nur Fauziah; Indarto Indarto; Joko Tri Atmojo; Aris Widiyanto (Indonesian Journal of Medicine, 2022)
Background: Tuberculosis or TB is a disease caused by the Mycobacterium tuberculosis complex. There are several comorbidities that experience severity and death when infected with tuberculosis or TB, namely hypertension, diabetes mellitus, cardiovascular disease, chronic kidney disease, cerebrovascular disease, and other diseases. This study aims to estimate the magnitude of the risk of treatment failure in Tuberculosis patients with Diabetes Mellitus comorbidity, with a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This was a systematic review and meta-analysis with the following PICO, population: tuberculosis patients. Intervention: chronic comorbid diabetes mellitus. Comparison: without comorbid diabetes mellitus. Outcome: treatment failure. The articles used in this study were obtained from three databases, namely Google Scholar, PubMed, and Science Direct. Keywords to search for articles “Tuberculosis” OR “TBC” AND “Diabetes Mellitus” OR “DM” AND “Treatment failure”. The included article is a full-text English cohort study design from 2007 to 2021 and reports the adjusted odds ratio (aOR) in multivariate analysis. The selection of articles is done using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 7 cohort studies involving TB patients undergoing treatment from America, Europe, Africa and Asia were selected for systematic review and meta-analysis. The data collected showed that tuberculosis patients undergoing treatment with comorbid diabetes mellitus had a 1.57 time the risk of treatment failure compared to patients without comorbid diabetes mellitus (aOR= 1.57; 95% CI= 1.08 to 2.30; p= 0.002).Conclusion: Comorbidity Diabetes mellitus increases the risk of experiencing treatment failure in tuberculosis patients.Keywords: diabetes mellitus, tuberculosis, mortality.Correspondence: Sri Iswahyuni. School of Health Sciences Mamba’ul Ulum Surakarta. Jl. Ringroad Utara, Mojosongo, Jebres, Surakarta, Central Java, Indonesia. Email: iswahyunisri@yahoo.co.id. Mobile: +62 815-6720-715.Indonesian Journal of Medicine (2022), 07(04): 417-427https://doi.org/10.26911/theijmed.2022.07.04.07